The Routledge Handbook of International Law and Anthropocentrism - Chapaux, Vincent; Mégret, Frédéric; Natarajan, Usha (Taylor & Francis, 2023)
humanitarianism, armed conflict, artificial intelligence, posthuman legal scholarship, posthuman ecology monochrome wooden sculptures, remote cultures, formalist aesthetics, contextualist aesthetics, vertical bilateral symmetry, split representation, aesthetic status